TUBERCULOSIS: PREVENTION THROUGH INCREASING PUBLIC KNOWLEDGE WITH HEALTH PROGRAM COMMUNICATION EDUCATION - Rinda Lestari; Suryani Suryani; Yustitia Akbar; Nova Mustika; Marisa Marisa; Ghufran Aulia; BA Martinus (JURNAL KATALISATOR, 2023)
Tuberculosis (TB) is one of the infectious diseases that is still a global health problem. According to World Health Organization (WHO) data in 2020, there are about 10 million new cases of tuberculosis worldwide. TB is still the leading cause of death from infectious diseases in the world, even surpassing the death rate from COVID-19 at the time. In 2019, there were 5,403 TB cases in West Sumatra, in 2019 there were 5,190 TB cases in men (62.70%). Padang is the city with the highest number of TB cases in West Sumatra, with 2,358 cases in 2018, In May 2022, there were 1,500 confirmed TB patients in Padang. Factors contributing to the increase in TB cases in Indonesia, including West Sumatra, are genetics, lifestyle, and level of knowledge. There has been a lot of discussion about tuberculosis, but not many have studied health program communication education about public knowledge about tuberculosis. The purpose of this study was to study health program communication education about public knowledge about tuberculosis. The survey method was used to collect data from respondents representing the community in Padang City. Surveys through written questionnaires and interviews via Google form sent online. Questions in the survey covered aspects such as public knowledge about tuberculosis before and after Promkes education, attitudes towards TB prevention, and factors influencing participation in education programs. The data were analyzed statistically, measuring changes in knowledge before and after Promkes education, and analyzing the factors that influenced the results. Health Program Education Group: Average knowledge about tuberculosis prevention: 8.5 Standard deviation of knowledge: 1.2. Uneducated Group: Average knowledge about tuberculosis prevention: 6.2 Standard deviation of knowledge: 1.5. From the results of the analysis, it can be seen that the group that received Promkes education had a higher average knowledge about tuberculosis prevention compared to the group that did not get education. This difference shows that Promkes education has the potential to have a positive impact on public knowledge about tuberculosis prevention.